Centralizers and isomorphism preservation of minimal factors of nearring modules. Issue 7 (3rd July 2021) - Peterson, Gary L.; Scott, Stuart D.
Abstract: If N 1 is a nearring, V is a faithful tame N 1 -module and N 2 is a nearring containing N 1 such that V is a faithful tame N 2 -module and the N 1 - and N 2 -ideals of V coincide, we study when N 1 -isomorphic minimal factors of V are N 2 -isomorphic. We also study a stronger form of such preservation called type preservation. Particular attention is paid to the case where N 2 is the nearring of 0-preserving and congruence preserving functions of V, C 0 ( V ). Here we will see that isomorphism preservation is related to centralizers of minimal factors relative to C 0 ( V ) which then motivates the study of these centralizers as well.